Diagnostic pathology. - Thompson, Lester D. R.; Muller, Susan; Nelson, Brenda (Netherland Elsevier, 2022)
"This expert volume in the Diagnostic Pathology series is an excellent point-of-care resource for practitioners at all levels of experience and training. Covering all areas of head and neck pathology, it incorporates the most recent clinical, pathologic, and molecular knowledge in this challenging field to provide a comprehensive overview of all key issues relevant to today's practice. Richly illustrated and easy to use, the third edition of Diagnostic Pathology: Head and Neck is a one-stop reference for accurate, complete pathology reports-ideal as a day-to-day reference or as a reliable teaching resource"--
Revised edition of: Diagnostic pathology. Head & neck / Lester D.R. Thompson ... [et al.] 2nd edition. [Philadelphia, PA] : Elsevier, [2016].
Keywords: Pathology -- Diagnostic